2021
DOI: 10.2196/24649
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Use Wiki-Based Knowledge Tools: Survey of Quebec Emergency Health Professionals

Abstract: Background Clinical decision support systems are information technologies that assist clinicians in making better decisions. Their adoption has been limited because their content is difficult to adapt to local contexts and slow to adapt to emerging evidence. Collaborative writing applications such as wikis have the potential to increase access to existing and emerging evidence-based knowledge at the point of care, standardize emergency clinical decision making, and quickly adapt this knowledge to l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Our findings suggest that while there may already be "buy-in" for EDCTS even from less technology-literate staff, their use is still not widespread [19][20][21]. Implementation efforts might benefit then, from focusing on environmental contextual factors rather than trying to change provider attitudes and beliefs.…”
Section: Overviewmentioning
confidence: 88%
“…Our findings suggest that while there may already be "buy-in" for EDCTS even from less technology-literate staff, their use is still not widespread [19][20][21]. Implementation efforts might benefit then, from focusing on environmental contextual factors rather than trying to change provider attitudes and beliefs.…”
Section: Overviewmentioning
confidence: 88%
“…Our findings suggest that while there may already be “buy-in” for EDCTS even from less technology-literate staff, their use is still not widespread [ 19 - 21 ]. Implementation efforts might benefit then, from focusing on environmental contextual factors rather than trying to change provider attitudes and beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…37 In this study, the significant direct impact of VC on DCP use by physicians revealed the combined function of attitudes, subjective norms and perceived behavioral control, which have been reported as important predictors of technology use in prior research. [39][40][41] Physicians will be more apt to adopt and use a technology in their clinical practice if they rate it highly and deem it can be implemented successfully. In addition, the direct influence of EOP on physicians' DCP use was confirmed by both support mechanism and practical implementation.…”
mentioning
confidence: 99%